Biomimetic strategies to produce catalytically reactive CuS nanodisks. Issue 8 (26th June 2019) - Bell, Elise C.; Munro, Catherine J.; Slocik, Joseph M.; Shukla, Dharmendra; Parab, Atul D.; Cohn, Joshua L.; Knecht, Marc R.
Abstract : Simple acid-containing amino acids are capable of producing CuS nanodisks with plasmon bands shifted into the near IR. The materials also demonstrated photocatalytic reactivity for the degradation of model organic compounds. Abstract : Copper sulfide materials have diverse applications from cancer therapy to environmental remediation due to their narrow bandgap and easily tuned plasmon. The synthesis of these materials often involves toxic reagents and harsh conditions where biomimetic methods may provide opportunities to produce these structures under sustainable conditions. To explore this capability, simple amino acids were exploited as biological ligands for the ambient synthesis of CuS materials. Using an aqueous-based approach, CuS nanodisks were prepared using acid-containing amino acid molecules that stabilize the materials against bulk aggregation. These structures were fully characterized by UV-vis analysis, transmission electron microscopy, dynamic light scattering, atomic force microscopy, selected area electron diffraction, and X-ray diffraction, which confirmed the formation of CuS. The materials possessed a vibrant plasmon band in the near IR region and demonstrated enhanced photocatalytic reactivity for the advanced oxidation of organic dyes in water. These results demonstrate a room temperature synthetic route to optically important materials, which could have important application in catalysis, optics, nanomedicine, etc.